A novel role of Drosophila cytochrome P450-4e3 in permethrin insecticide tolerance. (December 2015) - Terhzaz, Selim; Cabrero, Pablo; Brinzer, Robert A.; Halberg, Kenneth A.; Dow, Julian A.T.; Davies, Shireen-A.
Abstract: The exposure of insects to xenobiotics, such as insecticides, triggers a complex defence response necessary for survival. This response includes the induction of genes that encode key Cytochrome P450 monooxygenase detoxification enzymes. Drosophila melanogaster Malpighian (renal) tubules are critical organs in the detoxification and elimination of these foreign compounds, so the tubule response induced by dietary exposure to the insecticide permethrin was examined. We found that expression of the gene encoding Cytochrome P450-4e3 ( Cyp4e3 ) is significantly up-regulated by Drosophila fed on permethrin and that manipulation of Cyp4e3 levels, specifically in the principal cells of the Malpighian tubules, impacts significantly on the survival of permethrin-fed flies. Both dietary exposure to permethrin and Cyp4e3 knockdown cause a significant elevation of oxidative stress-associated markers in the tubules, including H2 O2 and lipid peroxidation byproduct, HNE (4-hydroxynonenal). Thus, Cyp4e3 may play an important role in regulating H2 O2 levels in the endoplasmic reticulum (ER) where it resides, and its absence triggers a JAK/STAT and NF-κB-mediated stress response, similar to that observed in cells under ER stress. This work increases our understanding of the molecular mechanisms of insecticide detoxification and provides further evidence of the oxidative stress responses induced by permethrin metabolism. Graphical abstract: Highlights: We examined the Malpighian tubule response induced by exposure to the insecticide permethrin. Cyp4e3 expression is induced in Drosophila fed on oxidants and permethrin. Manipulation of Cyp4e3 levels impact significantly on the survival of the whole fly. Endoplasmic reticulum stress responses are induced by permethrin metabolism. We provide better understanding of the molecular mechanisms of insecticide detoxification.